Challenges and Opportunities for Teaching Practical Skills at Higher Education Institutions under the conditions of COVID-19 Pandemic - Kasradze, Tea; Gulua, Ekaterine (European Journal of Social Science Education and Research, 2023)
The lack of practical skills of graduates of higher education institutions is one of the main challenges of the modern education system of Georgia, which has become even more urgent in the face of the COVID -19 pandemic. Within the framework of the research, we studied the latest scientific literature, researches and reports of various state and international organizations on the experience and current state of practical skills’ teaching in Georgia; on the new requirements for the workforce under the pandemic and post-pandemic; and on the future directions of providing students with practical knowledge. The paper also presents an analysis of the results of our research on the attitude of students towards the internship and the approaches of higher education institutions in the evaluation of practical knowledge and skills acquired by the students within the framework of the educational program. Based on the best practice and challenges identified as a result of the research, we have developed appropriate recommendations that we think will facilitate the production of professional graduates equipped with practical skills.